Unveiling the New Generation of Stars in NGC 604 with Gemini-NIRI - Fariña, Cecilia (2012)
We present a near-infrared study focused on the detection and characterization of the youngest stellar component of the NGC 604 giant star-forming region in the Triangulum galaxy (M 33). By means of color-color diagrams derived from the photometry of JHKs images taken with the Gemini Near Infrared Imaging and Spectrometer (NIRI), we have found 68 candidate massive young stellar objects. The spatial distribution of these sources matches the areas where previous studies suggested that star formation might be taking place, and the high spatial resolution of our deep NIRI imaging allows us to pinpoint the star-forming knots. An analysis of the fraction of objects that show infrared excess suggests that the star formation is still active, supporting the presence of a second generation of stars being born, although the evidence for or against sequential star formation does not seem to be conclusive.